SIMULATION OF RAINWATER HARVESTING FOR SUFFICIENT WATER NEEDS IN RAISING CORN (Zea Mays) - -, Febrianto (The University of Lampung, 2015)
A rainwater harvesting systemconsisted of a planning land area and a rainwater collection pond area. This studyaimed to determine the optimum ratio of the planting area to the collection pond area. Researchwas conductedby running a 13 year simulation with daily time step. A 13 year (1999-2011) daily meteorological data setobtained fromtheMeteorology, Climatology and GeophysicsAgency (BMKG) Lampung Province,was used to runthe simulation. Programswritten using VISSIM4.0 (Visual Simulation). The results showed that the rainwaterharvesting system can suffice the irrigation water for maize. The smallest pond area (570 m2) required ifplanting was done in February, while the largest pond area (1620 m2) required if plantingwas done on August.KeyWords: Evapotranspiration, Corn, Irrigation, Rainwater harvesting.